Book Review: Fourie, C., and A. Rid (eds) 2017. What Is Enough: Sufficiency, Justice, and Health. New York: Oxford University Press. Issue 2 (3rd January 2020) - Sachs, Benjamin
Abstract: This review uses the excellent recent anthology, What Is Enough: Sufficiency, Justice, and Health, edited by Carina Fourie and Annette Rid, as a springboard for a discussion of a little-noticed problem for sufficientarian principles governing the distribution of health or health care. All sufficientarian principles must be assigned a scope: the set of individuals who are to be brought up to the level of sufficiency. When it comes to health and health care, sufficientarians will, rightly, want to reject broad scopes, because they will entail that we are accountable for securing health care for, for example, wild animals. Unfortunately, any narrow scope will seem morally arbitrary, because it will imply that among all the individuals who could benefit from health care we are obligated to provide it only to some of them. But, I suggest here that such arbitrariness is no problem for narrow-scope sufficientarianism in health or health care as long as the principle is cast as a non-fundamental principle of public policy as opposed to a fundamental moral principle.